(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Chitosan is a biodegradable polymer composed of β- (1,4) -D-glucosamine linkages (deacetylated unit) and N- acetyl-D-glucosamine (acetylated unit). It is commercially produced by the deacetylation of chitin and in the food industries it is used as a stabilizer, thickener, in water treatment and easily processed into nanofibers, gels, nanoparticles and films. The objective of this work was to evaluate the effect of gamma irradiation on morphological, rheological and color properties of chitosan and gels. Chitosan samples were irradiated at the 5, 10 and 15 kGy doses and performed by scanning electron microscopy (SEM), color and rheology. SEM analyzes showed that the chitosan particles have a network agglomerated with irregular arrangements, and the irradiated samples presented smaller granules. It was observed that gamma radiation induces changes in the intensity of the tonality of the chitosan powder and gels, increasing the brown coloration. These changes are observed by the decreasing values of L * (luminosity) with increasing radiation dose and, consequently, an increase in the values of b * (brown tone), C * and h *, indicating a higher intensity of color. As for the rheological behavior, all the gels were characterized as Newtonian fluids and the irradiation altered their viscosity, leaving them less viscous.